Effects of different pulse widths on acute tibial nerve stimulation for overactive bladder in cats - Dongsheng Shang; Haoyu Sun; Han Deng; Gongyue Liu; Limin Liao; Xing Li (European Journal of Medical Research)
Abstract Purpose This study aimed to assess the effectiveness of different pulse widths in suppressing bladder overactivity using tibial nerve stimulation (TNS) in cats. Methods Hook electrodes were implanted on the left tibial nerve. Cystometry was conducted by infusing either acetic acid (AA) or normal saline (NS). TNS was applied at intensities of 2–4 times the threshold (T) with pulse widths ranging from 60 to 624 µsec. Cystometrograms were used to evaluate the impact of different pulse widths on the micturition reflex. Results Bladder capacity (BC) was significantly reduced to 49.71% ± 6.76% of the NS control level (8.58 ± 1.70 mL) due to AA-induced bladder overactivity (P < 0.001). During AA infusion, TNS at pulse widths of 60, 210, 420, and 624 µsec significantly increased BC to 70.65% ± 9.06%, 73.22% ± 6.28%, 73.79% ± 8.56%, and 76.25% ± 7.95% of the NS control level, respectively (P < 0.001). No significant differences were observed among the four pulse widths (P > 0.05). The threshold intensity (T) was higher at 60 µsec than at 624 µsec (P < 0.01), while T at 210 µsec, 420 µsec, and 624 µsec showed no significant differences (P > 0.05). Conclusions All four pulse widths demonstrated inhibitory effects on bladder overactivity. However, no significant differences were observed among the four pulse widths.